The Relationship Between Religious Affiliation and Secular Attitudes and Behaviour - Anderson, Grace Merle (My University, 1964)
Consideration is given in this thesis to the relationship of religious affiliation of Catholics, Anglicans and Other Major Protestant denominations, to secular attitudes and reported behavior. The latter is analyzed in terms of the political, as manifested in voting preferences, and the economic, as illustrated by attitudes toward work and reported behavior in leisure periods. Leisure time activity was examined in the areas of reading, hobbies and visiting of friends and relatives. The data used in this study was obtained from The McMaster Study of Life in the City conducted in the North End of the City of Hamilton, Ontario in the summer of 1962.
Religious Affiliation and Secular Attitudes and Behaviour
Keywords: religious affiliation; Catholic; Anglican; Protestant; secular attitude; behaviour; politics; economics; leisure